2000
DOI: 10.1111/j.1365-2338.2000.tb00938.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of new PCR primers for identification of Monilinia species*

Abstract: New polymerase chain reaction (PCR) primers were developed for the identification of the EU quarantine pest Monilinia fructicola. These allowed nine M. ffucticola isolates to be distinguished from other fungi, including six isolates of M. laxa and six isolates of M. fructigena (which also cause brown rot of stone and pome fruit). Three M. fnrcticola isolates from Japan and one from Australia did not react with a primer set previously published for M. fructicola. M. fnrcticola isolates could be subdivided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
16

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 7 publications
1
38
0
16
Order By: Relevance
“…Molecular-genetic identification was carried out by polymerase chain reaction (PCR). DNA was isolated by standard isolation kits and specific sets of PCR primers according to Ioos and Frey (2000) for M. fructicola and Hughes et al (2000) for M. laxa and M. fructigena were used.…”
Section: Methodsmentioning
confidence: 99%
“…Molecular-genetic identification was carried out by polymerase chain reaction (PCR). DNA was isolated by standard isolation kits and specific sets of PCR primers according to Ioos and Frey (2000) for M. fructicola and Hughes et al (2000) for M. laxa and M. fructigena were used.…”
Section: Methodsmentioning
confidence: 99%
“…A single colony was stored on potato dextrose agar plates at 4°C. Molecular analysis according to Hughes et al (2000) suggested that the isolate corresponded to M. fructigena (not shown). Mycelial plugs were used to infect previously disinfected peach fruits, in order to generate abundant spores for artificial inoculations.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Standard methods for precise identification of Monilinia species include: investigation of morphological and cultural features (Byrde and Willetts, 1977;De Cal and Melgarejo, 1999) and/or molecular methods (Hughes et al, 2000;Còté et al, 2004).…”
Section: Identification Of Monilinia Speciesmentioning
confidence: 99%